Electrochemical quantum dots-based magneto-immunoassay for detection of HE4 protein on metal film-modified screen-printed carbon electrodes - Čadková, Michaela; Kovářová, Aneta; Dvořáková, Veronika; Metelka, Radovan; Bílková, Zuzana; Korecká, Lucie (My University, 2018)
A novel enzyme-free electrochemical immunosensor was developed for highly sensitive detection and quantification of human epididymis protein 4 (HE4) in human serum. For the first time, core/shell CdSe/ZnS quantum dots were conjugated with anti-HE4 IgG antibodies for subsequent sandwich-type immunosensing with super paramagnetic microparticles functionalized with anti-HE4 IgG antibodies, which allow rapid and efficient HE4 capture from the sample. Electrochemical detection of anti-HE4 IgG - HE4 - anti-HE4 IgG(CdSe/ZnS) immunocomplex was performed by recording the current response of Cd(II) ions, released from dissolved quantum dots at screen-printed carbon electrode (SPCE), modified with mercury or bismuth film. The linear range of the detection was from 20 pM to 40 nM with limit of detection of 12 pM using three times the standard deviation of blank criterion at mercury-film SPCE and from 100 pM to 2 nM with limit of detection of 89 pM at bismuth-film SPCE. Proposed electrochemical immunosensor meets the requirements for fast and sensitive quantification of HE4 biomarker in early stage of ovarian cancer and due to the proper sensitivity and specificity presents a promising alternative to enzyme-based probes used routinely in clinical diagnostics.
Elektrochemický magneto-imunosenzor pro detekci proteinu HE4 založený na kvantových tečkách a tištěných uhlíkových elektrodách s kovovým filmem
Keywords: Magneto-immunoassay; HE4 biomarker; Quantum dots; Metal-film electrode; Anodic stripping voltammetry; Magneto imunoanalýza; biomarker HE4; kvantové tečky; elektrody s kovovým filmem; anodická rozpouštěcí voltametrie